Wearing an ice vest improves cycling capacity in the heat - Cuttell, S.; Victor, K.; Tyler, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Increased core body temperatures are widely accepted as a limitation of exercising in the heat (Armstrong et al., 1995). Interventions such as acclimation and cooling have been shown to attenuate the reduction in exercise performance and capacity observed. Most of the literature has focused on pre-cooling; however, such approaches are often impractical. Practical cooling of the neck during exercise has been shown to enhance running capacity in the heat (Tyler and Sunderland, 2011) but the torso covers a much larger area of the body`s surface and so theoretically may be a more effective site to cool than the neck. The aim of study was to investigate the effects of ice vest cooling on cycling capacity in the heat. Methods: Twelve untrained, healthy, unacclimatised males (24 ± 3.7 years, 83.1 ± 12.1 kg mass, 1.82 ± 0.08 cm stature) completed an incremental cycle test to determine maximum power output (Wmax: 240 ± 25 W). Following this test and a full familiarisation participants completed two experimental cycle capacity tests; one with (VC) and one without (CG) an ice vest. During the familiarisation and main trials the participants cycled in a hot environment (35.0 ± 0.1°C; 50 ± 1% rh) to volitional exhaustion at 60% Wmax. Physiological (HR, body mass, rectal and skin temp) and perceptual (RPE, feeling scale, thermal sensation of torso and skin) variables were measured at 5 minute intervals. Significance was set at the P < 0.05 level. Results: Mean cycling capacity was longer in VC (28.91 ± 10.48 min) compared to CG (23.54 ± 8.86 min) (P=.024; d= 0.46). There was a significant difference between trials and temperature at the torso (CG: 36.26 ± = .80 C°; VC: 31.15 ± = 1.50 C°; P =.001 d = 3.63). There was no effect between any other physiological variables (p=0.05). There was a significant difference between CG and IV for skin temperature at the torso (CG: 36.26 ±.80 C°; IV: 31.15 ± 1.50 C°; P=0.01) and thermal sensation of the torso (CG: 6.74 ± .992; IV: 4.62 ± .881; P=0.001). Other perceptual variables reported no significant differences between conditions CG and IV (p=0.05). Discussion: The present study indicates that the use of an ice vest can have a beneficial effect while exercising in the heat. Cardiovascular measures appear not to be effected, thus the study points towards thermal sensation of the torso having sufficient effect to enhance performance in the heat.